Pengaruh Kinerja Keuangan terhadap Return Saham pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Hutama Faizal Ilham (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The purpose of this study is to analyze the liquidity ratio, solvency ratio, profitability ratio, and activity ratio on stock returns. The population of this study was 32 food and beverage companies listed on the Indonesia Stock Exchange, for three years, from 2020 to 2022. The sampling technique used was purposive sampling, by drawing samples from the population based on certain criteria. The sample obtained in this study was 21 food and beverage companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. The test results indicate that the liquidity ratio, proxied by the current ratio, has no effect, the solvency ratio, proxied by debt to equity, has a positive effect, the profitability ratio, proxied by return on equity, and the activity ratio, proxied by total assets turnover, has no effect on stock returns in food and beverage companies listed on the Indonesia Stock Exchange during the period 2020-2022.